PENGARUH GAJI TERHADAP PRODUKTIVITAS KERJA PADA PERUSAHAAN ANGKUTAN UMUM PO. RUDI DI RANGKASBITUNG KABUPATEN LEBAK - Indah Lestari; Asep Erik Hidayat (The Asia Pacific Journal Of Management Studies, 2018)
There are still disparities of income received by employees, especially in the mechanical parts. Which in practice both old and new employees there are differences in income that impact on the productivity of new employees. And mutual rely on the work appeared as lacking fairness of the payment by the company, in which employment and hours of work they do together and help each other. And productivity levels seen in public transport companies PO. Rudi showed a decrease and less than the maximum. This study has the formulation of the problem: 1. How remuneration in the public transport company PO. Rudi 2. How does the productivity of labor on public transport company PO. Rudi 3. Is there any influence on the productivity of labor wages in the public transport company PO. Rudi. This study aims: 1. To find out how the remuneration on public transport company PO. Rudi. 2. To know how is labor productivity in the public transport company PO. Rudi. 3. To determine the effect of the salary increase employee productivity in the public transport company PO. Rudi.The method used in this study is causal and quantitative research with a sample of 80 respondents, using the technique of saturated sample, the data collection technique used observation, questionnaire, literature study, data analysis techniques using regression analysis, Spearman correlation rank, the coefficient of determination, t test.